Evaluasi Pengaruh Variasi Konsentrasi Bentonit terhadap Densitas Lumpur Pemboran Berbasis Air - Huldiah, Huldiah; Fitria, Debby Nur; Wiranto, Wiranto (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
In petroleum operations, drilling is a fundamental process that determines the success of reaching reservoir targets. Drilling performance is greatly influenced by the characteristics of drilling mud, such as density. The composition of mud constituents, including bentonite, has the potential to affect fluid density characteristics. This study aims to evaluate the effect of variations in bentonite concentration on the density of water-based drilling mud. The experiment was conducted using a laboratory approach with a mud balance on two mud samples with different bentonite compositions. The results showed that variations in bentonite concentration did not produce significant changes in density, with both samples exhibiting relatively similar density values. This indicates that mud density is more influenced by weighting materials than by bentonite concentration. These findings provide insight into the role of bentonite in drilling mud design.